Evaluation of Modification of the 3M™ Molecular Detection Assay (MDA) Salmonella Method (2013.09) for the Detection of Salmonella in Selected Foods: Collaborative Study. (27th November 2019) - Bird, Patrick; Fisher, Kiel; Boyle, Megan; Huffman, Travis; Benzinger, M Joseph; Bedinghaus, Paige; Flannery, Jonathon; Crowley, Erin; Agin, James; Goins, David; Benesh, DeAnn; David, John; et al.
Abstract: The 3M ™ Molecular Detection Assay (MDA) Salmonella utilizes isothermal amplification of nucleic acid sequences with high specificity, efficiency, rapidity and bioluminescence to detect amplification of Salmonella spp. in food, food-related, and environmental samples after enrichment. A method modification and matrix extension study of the previously approved AOAC Official Method SM 2013.09 was conducted, and approval of the modification was received on March 20, 2014. Using an unpaired study design in a multilaboratory collaborative study, the 3M MDA Salmonella method was compared to the U.S. Department of Agriculture/Food Safety and Inspection Service (USDA/FSIS) Microbiology Laboratory Guidebook (MLG) 4.05 (2011), Isolation and Identification of Salmonella from Meat, Poultry, Pasteurized Egg, and Catfish Products for raw ground beef and the U.S. Food and Drug Administration (FDA)/ Bacteriological Analytical Manual (BAM) Chapter 5, Salmonella reference method for wet dog food following the current AOAC guidelines. A total of 20 laboratories participated. For the 3M MDA Salmonella method, raw ground beef was analyzed using 25 g test portions, and wet dog food was analyzed using 375 g test portions. For the reference methods, 25 g test portions of each matrix were analyzed. Each matrix was artificially contaminated with Salmonella at three inoculation levels: an uninoculated control level (0 CFU/test portion), a low inoculum level (0.2–2 CFU/test portion), and a high inoculum level (2–5 CFU/test portion). In this study, 1512 unpaired replicate samples were analyzed. Statistical analysis was conducted according to the probability of detection (POD). For the low-level raw ground beef test portions, the following dLPOD (difference between the LPODs of the reference and candidate method) values with 95% confidence intervals were obtained: –0.01 (–0.14, +0.12). For the low-level wet dog food test portions, the following dLPOD with 95% confidence intervals were obtained: –0.04 (–0.16, +0.09). No significant differences were observed in the number of positive samples detected by the 3M MDA Salmonella method versus either the USDA/FSIS-MLG or FDA/BAM methods.